2013
DOI: 10.1016/j.wear.2012.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Indentation and scratch testing of DLC-Zr coatings on ultrafine-grained titanium processed by high-pressure torsion

Abstract: High-pressure torsion was employed to refine the microstructure of grade 2 Ti under an imposed pressure of 3.0 GPa at room temperature. The microhardness of grade 2 Ti increased from 1.82 GPa for the coarse grain state to 3.05 GPa after high-pressure torsion processing, where this value is very close to the hardness of the Ti-6Al-4V alloy.Subsequently, several diamond-like carbon (DLC) coatings with thicknesses of ~1.4 Pm were deposited on as-received Ti, high-pressure torsion processed Ti and Ti-6Al-4V sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 51 publications
3
31
0
2
Order By: Relevance
“…The maximum von Mises stresses are typically far into the substrate at the critical load and substrate yield occurs before the coatings fail [39]. In a recent study, Wang and co-workers reported that the critical load for coating failure on a range of DLC and TiN coatings on titanium alloys did not depend on coating composition, but correlated directly with the hardness of the substrate [40]. The significance of substrate yield was emphasized by cross-sectional profiles of the scratch depth at failure which were much larger than the coating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum von Mises stresses are typically far into the substrate at the critical load and substrate yield occurs before the coatings fail [39]. In a recent study, Wang and co-workers reported that the critical load for coating failure on a range of DLC and TiN coatings on titanium alloys did not depend on coating composition, but correlated directly with the hardness of the substrate [40]. The significance of substrate yield was emphasized by cross-sectional profiles of the scratch depth at failure which were much larger than the coating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Morshed [9] sugere que ao otimizar as condições de ataque iônico com argônio é possível maximizar a adesividade e minimizar tensões residuais, sem alterar de forma significativa a dureza destes filmes. Apesar da extensa literatura sobre o aumento da adesividade, a caracterização desta propriedade se mantém principalmente qualitativa [10][11][12]. Entre diversos ensaios, a indentação Rockwell C, descrita na norma VDI3198, e os ensaios de riscamento são as maneiras mais comuns de se medir a adesividade de filmes de DLC [10][11][12][13][14].…”
Section: Introductionunclassified
“…Apesar da extensa literatura sobre o aumento da adesividade, a caracterização desta propriedade se mantém principalmente qualitativa [10][11][12]. Entre diversos ensaios, a indentação Rockwell C, descrita na norma VDI3198, e os ensaios de riscamento são as maneiras mais comuns de se medir a adesividade de filmes de DLC [10][11][12][13][14]. No presente estudo, ao invés de comparar aspectos morfológicos das indentações com padrões estabelecidos pela norma VDI3198, foi realizada uma comparação numérica através da quantificação da área desplacada através da análise de imagens produzidas por microscopia ótica.…”
Section: Introductionunclassified
“…Hybrid coatings combined with layers of W and Zr-DLC are used to improve the coating properties, surface smoothness and tightness included. The use of diamond-like coatings (which is a novel solution in the field of surface engineering, offering high thermal resistance, good conductivity, and high hardness) has considerably improved the quality of the tested materials [15,16].…”
Section: Introductionmentioning
confidence: 99%